PHUBBING PADA GEN Z APAKAH DIPREDIKSI OLEH FOMO? - Evi Septiani Lauw; Miftakhul Jannah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: Phone snubbing or phubbing is the impact of increasingly developing technological developments, the urge to play with smartphones when communicating can be caused by the fear of missing out. Objective: This research was conducted to determine the effect of fear of missing out (FoMO) on phubbing behavior in Gen Z. Method: The respondents of this research were Gen Z at University X, Surabaya City, as many as 312 people using clustering sampling techniques for sampling. This research is a non-experimental quantitative research. Research data was collected using the FoMO and phubbing scales. Data were analyzed using simple regression techniques with the help of SPSS 26.0. Results: Based on the results of the regression test, a value of 0.176 was found and the correlation coefficient was positive and in the same direction. Conclusion: There is an influence of FoMO on phubbing behavior in Gen Z and because a positive correlation coefficient value was found, the higher the FoMO, the higher the phubbing behavior. The R Square found shows that FoMO influences phubbing behavior in Gen Z by 17.6%.